Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1750-3639.2009.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Lesion Profiling at Primary Isolation in RIII Mice is Insufficient in Distinguishing BSE from Classical Scrapie

Abstract: Primary isolation of bovine spongiform encephalopathy (BSE) in RIII mice generates a lesion profile believed to be reproducible and distinct from that produced by classical scrapie. This profile, which is characterized by peaks at gray matter areas 1, 4 and 7 (dorsal medulla, hypothalamus and septal nuclei), is used to diagnose BSE on primary isolation. The aim of this study was to investigate whether the BSE agent could be present in sheep diagnosed with classical scrapie, using lesion profiles in RIII mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 23 publications
(58 reference statements)
6
54
1
Order By: Relevance
“…To explain strain diversity of prions the prion-only hypothesis postulates that, in the absence of a nucleic acid, the conformation of the abnormally folded, infectious form of the prion protein (PrP sc ) codes for strainspecific information (Wille et al, 2002). Following inoculation and serial passage of different sheep scrapie isolates, around 20 scrapie strains (Bruce, 2003) have been isolated and characterized by their relative incubation periods and pattern of brain vacuolation in different inbred lines of mice (Fraser, 1976), and more recently by the immunohistochemical (IHC) pattern of disease-associated PrP (PrP d ) accumulation in the brain (Beck et al, 2010). However, the significance of mouse-adapted scrapie strains remains obscure, since the disease phenotype arising from the In 2006, a working group was established under the auspices of the Network of Excellence Neuroprion with the aim of standardizing criteria and methods for the definition and characterization of sheep scrapie strains in the natural host.…”
Section: Introductionmentioning
confidence: 99%
“…To explain strain diversity of prions the prion-only hypothesis postulates that, in the absence of a nucleic acid, the conformation of the abnormally folded, infectious form of the prion protein (PrP sc ) codes for strainspecific information (Wille et al, 2002). Following inoculation and serial passage of different sheep scrapie isolates, around 20 scrapie strains (Bruce, 2003) have been isolated and characterized by their relative incubation periods and pattern of brain vacuolation in different inbred lines of mice (Fraser, 1976), and more recently by the immunohistochemical (IHC) pattern of disease-associated PrP (PrP d ) accumulation in the brain (Beck et al, 2010). However, the significance of mouse-adapted scrapie strains remains obscure, since the disease phenotype arising from the In 2006, a working group was established under the auspices of the Network of Excellence Neuroprion with the aim of standardizing criteria and methods for the definition and characterization of sheep scrapie strains in the natural host.…”
Section: Introductionmentioning
confidence: 99%
“…1A), but densitometry of these lanes to generate an SHa31/P4 ratio suggested that this method distinguished only the samples containing up to 80% BSE agent from scrapie agent (data not presented). In addition to dual-antibody staining, measurement of the glycoform ratios of the monoglycan and diglycan PrP Sc species can also be used to discriminate prion strains (19,20). Densitometry of the Western blot signals for the monoglycan and diglycan PrP Sc species within brain mixes provided data that were plotted on a scatter plot, which demonstrated that isolates of BSE and scrapie were clearly differentiated from each other (Fig.…”
Section: A Standard Methodology For the Differentiation Of Bse From Smentioning
confidence: 99%
“…However, the lack of susceptibility of conventional mouse models to most of the sCJD isolates (Bruce et al, 1997;Hill et al, 1997) and to several scrapie isolates (Bruce et al, 1997;Beck et al, 2010b), has limited the usefulness of this approach for investigating the potential similarities of small ruminant and human TSE agents.…”
Section: Biological Comparisonmentioning
confidence: 99%